Total Nitrogen Stock in Soil Profile Affected by Land Use and Soil Type in Three Counties of Mollisols - Li, Meng; Han, Xiaozeng; Li, Lu-Jun (Frontiers in Environmental Science, 2022)
Soil total nitrogen is the major indicator of soil fertility and quality in agricultural ecosystems. However, few comparative studies investigated the spatial patterns of soil total nitrogen density (STND) in deep soils of different land uses and soil types. Therefore, our study aimed to identify the influence of environmental factors on spatial variability in STND by comparing the STND spatial patterns of different land uses and soil types in a typical Mollisols in northeast China. Results showed that land use types did not significantly affect STND, but the soil types did. The STND was more heterogeneous above 60 cm than that in subsoil, and no significant changes in STND were found in the same land use or soil type. The STND had a significant correlation with SOC, soil BD and pH regardless of land use or soil type. The STND in the soil profile (100 cm) and top 20 cm was fitted using a mathematical model. The results provided insights into nitrogen cycle and stock in similar areas in northeast China.